Desórdenes alimenticios y su incidencia en la gastritis en adultos de 40 a 60 años en la comunidad 7 de octubre del cantón Quevedo provincia Los Ríos, periodo septiembre 2017 a febrero 2018 - Zambrano Uriña, Karina Rosario (2018)
To carry out the following work was carried out in the sector of the October 7 Canton Quevedo, place where they live a large population of adults, where 50 people whose ages ranged between 40 to 60 years, which had eating disorders and symptoms of stomach inflammation due to this parameters we could choose a vulnerable population and risk factors such as alcohol, snuff, poor diet and increased bacteria, identifying patients who are likely to be diagnosed with gastritis by the presence of helicobacter pylori. After being identified, we subdivided the 50 people who became our sample; to which they were given the necessary information and training to let them know what they can do if they are diagnosed with gastritis and how they could avoid it. The people who attended the training were conducted a survey to determine what state of health they were and if they had done a test to determine helicobacter pylori since this is one of the most common tests to know if you have any kind of problem gastrointestinal by the increase of Pylori bacteria, to determine the relationship they have in gastric diseases in order to avoid more serious diseases. The samples were processed in the cloud laboratory, with rapid immunocomatography tests, to determine the presence of helicobacter pylori bacteria. The results obtained show that the most relevant figures are in the group of people who have gastric problems, being that 65% of the patients present positive for helicobacter pylori in faeces while the other 35% is negative, through this training guarantees to reduce patients with gastric problems contributing to the well-being of the community. Therefore it is recommended to use the material dictated in the training to prevent gastric diseases and in the case of confirming to follow an adequate treatment to improve their health and lifestyle.